(untitled) (Journal of Nepal Geological Society, 2019)
Huge amounts of construction materials are required to fulfill construction works, which are being undertaken by local and Government levels. In this regard, searching for good quality construction materials is a tough job. The Budhi Gandaki-Narayani River is rich in carrying natural fine aggregates from the Higher and the Lesser Himalayas, which are extensively exposed along its bank. Currently ongoing and future hydro power projects, will require a tremendous amount of fine aggregates. In light of this, the present study was made to evaluate fine aggregates of the Budhi Gandaki-Narayani River. The gradation curves of fine aggregates from this river varied from well graded to uniform graded. Compositional analysis shows that quartz is dominant over other minerals. Rock fragments are composed of gneiss, schist, quartzite, metasandstone, phyllite, shale, granite, etc. Deleterious materials excluding organic matter range from 0.3 % to 1.5 % and organic matter present in range from 0.57 % to 1.11 %. The trend of presence of inorganic deleterious material and organic matter is increasing towards southern segments of the river, but they remain below 2%. Mean roundness of particles ranges from 1.88 to 2.54. Bulk dry density of fine aggregate is below 2 gm/cm³. Similarly, the specific gravity ranges between 1.49 and 1.79. Fineness modulus ranges between 1.36 and 3.50 showing that, coarse, medium, fine and very fine sediments are distributed along the stretch of river. Water absorption value of fine aggregate ranges from 0.48 % to 2.87 %. When using fine aggregates from southern segments of the Budhi Gandaki-Narayani River, reduction of mica and beneficiation process will enhance and provide better result for smooth plastering, rendering and screeding.